Impact of a Ketogenic Diet on Sporadic Inclusion Body Myositis: A Case Study - Phillips, Matthew C. L.; Murtagh, Deborah K. J.; Ziad, Fouzia; Johnston, Samuel E.; Moon, Ben G. (Frontiers in Neurology, 2020)
Sporadic inclusion body myositis (IBM) is a chronic inflammatory and degenerative muscle disease with limited treatment options; no therapy can alter its natural course. Ketogenic diets are theoretically capable of suppressing inflammation, enhancing cell bioenergetics, alleviating mitochondria dysfunction, and stimulating autophagy, which may be beneficial in IBM. We report the case of a 52-year-old woman with worsening IBM who pursued a modified ketogenic diet for 1 year. Adverse effects were mild and resolved 3 weeks into the diet. Prior to starting her ketogenic diet, despite the use of a walking stick at all times, she was experiencing one-to-two falls per week as well as swallowing difficulties, musculoskeletal pain, and depression. Moreover, magnetic resonance imaging (MRI) of the bilateral thighs during the year prior to the diet indicated worsening muscle inflammation and a 14% decrease in her thigh muscle volume, which corresponded to a 4% decrease in her ratio of thigh muscle to thigh total volume. After 1 year on her ketogenic diet, our patient regained independent walking and her swallowing difficulties, pain, and depression resolved. She maintained her strength, improved in every test of function, enhanced her quality of life, and lowered her blood creatine kinase. MRI of the bilateral thighs during the year of the diet indicated stabilized muscle inflammation and a 2.9% decrease in her thigh muscle volume, which in the context of diet-induced fat loss corresponded to a sustained 1% increase in her ratio of thigh muscle to thigh total volume. This case is unique in that a ketogenic diet was utilized as the primary treatment strategy for a patient with confirmed IBM, culminating in substantial clinical improvement, stabilized muscle inflammation, and a slowed rate of muscle atrophy. Our patient has remained on her ketogenic diet for over 2 years now, and continues to enjoy a full and independent life.